Growth and Welfare Effects of Health Care in Knowledge Based Economies - Michael Kuhn; Klaus Prettner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We study the effects of a labor-intensive health care sector within an R&D-driven growth model with overlapping generations. Health care increases longevity and labor participation/productivity. We examine under which conditions expanding health care enhances growth and welfare. Even if the provision of health care diverts labor from productive activities, it may still fuel R&D and economic growth if the additional wealth that comes with expanding longevity translates into a more capital/machine-intensive final goods production and, thereby, raises the return to developing new machines. We establish mild conditions under which an expansion of health care beyond the growth-maximizing level is Pareto-improving.
Keywords: I11; O41; O11; 330